2016
DOI: 10.1063/1.4965917
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the geometric structure of neutral niobium carbide clusters via infrared spectroscopy

Abstract: We report experimental vibrational spectra of small neutral niobium carbide clusters in the 350-850 cm spectral range. Clusters were first irradiated by IR light and subsequently probed using UV light with photon energies just below the ionization threshold. Upon resonance with an IR vibrational mode, the number of cluster ions increases, allowing to record a vibrational spectrum. In complementary density functional theory calculations, we have simulated the IR spectra for several low-energy isomers. We were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…We note that no current experimental techniques exist that can independently determine the geometry of gas-phase clusters, including the bond lengths and bond angles. Experimental techniques such as ion mobility, electron diffraction, Raman spectroscopy, , and infrared spectroscopy provide information on cluster geometries; however, they do require theoretical input.…”
Section: Unique Properties Of Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…We note that no current experimental techniques exist that can independently determine the geometry of gas-phase clusters, including the bond lengths and bond angles. Experimental techniques such as ion mobility, electron diffraction, Raman spectroscopy, , and infrared spectroscopy provide information on cluster geometries; however, they do require theoretical input.…”
Section: Unique Properties Of Clustersmentioning
confidence: 99%
“…Bakkeret al studied C 60 , neutral and cationic niobium clusters, and ferrimagnetic cage-like Fe 4 O 6 cluster . Geometries of partially oxidized rhodium cluster cations, Rh 6 O m + ( m = 4, 5, 6), were illustrated by Koyama et al In the study of neutral niobium carbide clusters Nb n C m ( n = 3–6, m = 3–7), Chernyy et al confirmed experimentally the appearance of bulk-like crystal NbC structure for small clusters down to 12 atoms …”
Section: Unique Properties Of Clustersmentioning
confidence: 99%
“…This was demonstrated to be consistent with its relatively larger HOMO–LUMO gaps and ionization energy. , Among others, the dehydrogenation of the mono-, di-, and trimethyl-substituted benzenes on cationic niobium clusters was studied by an FT-ICR mass spectrometer, showing dramatic size dependence of partial or complete dehydrogenation for these clusters . Extensive studies have also been devoted to understanding size-dependent stability and properties of niobium-involved clusters and complexes. For example, photoelectron spectra of the anionic niobium clusters Nb n – and doped systems were studied, showing a variety of patterns correlated with geometrical structures. However, the magic number of ionic niobium clusters has not been experimentally identified by far to the best of our knowledge.…”
Section: Introductionmentioning
confidence: 81%
“…Conversely, one can also wonder whether it is the closeness of the low‐lying electronic state to the “bright” vibrational states leads to an enhanced vibronic coupling. While we are unable to predict this strength, or its consequences, we do note that in our experiments to probe vibrational bands of Ta 5 C 3 we used IR pulse energies that were an order of magnitude lower than required for observation of the vibrations for niobium carbide clusters,), even though the calculated IR intensities are similar. We believe that the possibility to use such a low pulse energy in the case of Ta 5 C 3 is enabled by the presence of the low‐lying electronic state, providing an enhanced intramolecular energy redistribution process.…”
Section: Figurementioning
confidence: 99%